A preliminary investigation of Cyberchondria and its correlates in a clinical sample of patients with obsessive–compulsive disorder, anxiety and depressive disorders attending a tertiary psychiatric clinic. (1st June 2022) - Vismara, Matteo; Benatti, Beatrice; Ferrara, Luca; Colombo, Anna; Bosi, Monica; Varinelli, Alberto; Pellegrini, Luca; Viganò, Caterina; Fineberg, Naomi A.; Dell'Osso, Bernardo
Abstract: Objectives. This cross-sectional study aimed to investigate the frequency and presentation of cyberchondria (CYB) in patients with obsessive–compulsive disorder (OCD), anxiety disorders (ADs), and major depression disorder (MDD). Methods. Seventy-seven patients (OCD:25, ADs:26, MDD:26) referred to a tertiary psychiatry outpatient clinic and 27 healthy controls (HCs) were included. A 'working' definition of CYB was used to measure CYB frequency. CYB severity was measured with the Cyberchondria Severity Scale (CSS). Results. CYB as currently defined was present in just 1.3% of the combined patients' sample. Using a broader definition (omitting the disability criterion), we found a higher distribution (OCD:12%, ADs:19.2%, MDD:15.4%, HCs:3.7%) and greater CYB symptom severity. Patients with OCD (63.3 ± 18.9) and ADs (63.3 ± 25.9) showed a higher CYB severity, compared with HCs (48.4 ± 9.9, p <.05). In the combined patients' sample, a positive correlation was found between the CSS scores and measures of health anxiety or hypochondriasis. Higher CYB symptom severity emerged in patients with a positive family history of psychiatric disorders and in those prescribed benzodiazepines or mood-stabilisers. Conclusion. CYB represents a common transdiagnostic syndrome in patients with OCD, ADs, and MDD with a spectrum of severity and indicates a variable burden of illness, supporting the need for specific clinical considerations and interventions. Key points: Cyberchondria (CYB) represents a common transdiagnostic syndrome in patients with obsessive–compulsive disorder, anxiety, and depressive disorders. CYB's frequency as a syndrome of compulsive online health searches associated with an increased anxiety and distress was reported in 10–20% patients. Health anxiety/hypochondriasis showed a strong correlation with CYB. Patients with a positive family history of psychiatric disorders and those prescribed benzodiazepines or mood-stabilisers showed higher CYB symptom severity. Considering the spread of Internet use for health-related information, additional studies investigating CYB in clinical samples are encouraged.